Brain iron deposits are associated with apathy in cognitively normal and impaired adults. (December 2021) - Sur, Sandeepa; Chen, Lin; Yu, Danyang; Rubin, Leah H.; Xu, Yanxun H.; Lin, Zixuan; Yasar, Sevil; Rosenberg, Paul B.; Kalyani, Rita; Van Zijl, Peter; Albert, Marilyn S.; Lu, Hanzhang; et al.
Abstract: Background: Apathy is a common symptom in older cognitively normal and impaired individuals and can be distinguished from depression. Apathy is characterized by loss of interest and motivation, emotional unresponsiveness, executive deficits, and diminished dopaminergic and noradrenergic neurotransmission. Apathy is linked to vascular risk and fronto‐striatal deficits [(volume‐loss & white‐matter‐hyperintensities(WMH)], but mechanisms still relatively unknown. Prior studies link brain‐iron deposition to oxidative‐stress, vascular‐diseases, neurodegeneration, disrupted striatal‐dopamine neurotransmission, and report equivocal associations between depression and peripheral iron‐levels, which might not reflect cerebral iron‐deposits. Quantitative‐Susceptibility‐Mapping(QSM)‐MRI quantifies bulk tissue‐magnetic‐susceptibility from gradient‐echo(GRE) signal‐phase, successfully providing an estimate for iron‐content in gray‐matter tissue in neurodegenerative disorders, and major‐depressive‐disorder. This study probes a possible mechanistic connection between apathy‐symptoms and cerebral iron‐deposits. Method: A cross‐sectional study was conducted in 73 participants (71.7±7.13 years; 24‐normal, 38‐MCI, 11‐mild‐dementia)(Table‐1). Geriatric Depression Scale: (GDS, 15‐items), assesses constellation of depressive symptoms including apathy. 3Tesla‐Philips scanner acquired MRI‐images using a 3D T1‐weighted Magnetization‐Prepared‐Rapid‐Acquisition‐of‐Gradient‐Echo(MPRAGE) sequence(1×1×1mm 3 ) for anatomic reference and a 3Dmulti‐echo gradient‐echo sequence(0.8×0.8×1.6 mm, TE1/TE/TR=6/6/30, 5‐unipolar‐echoes) for QSM, which were reconstructed using JHU/KKI QSM‐Toolbox(version3.0; http://godzilla.kennedykrieger.org/QSM/). Phase‐processing, QSM‐dipole‐inversion and brain‐segmentation was performed. Twelve regions‐of‐interest(ROI) were quantified for volume and tissue‐magnetic‐susceptibility(reference, CSF). Fluid‐Attenuated‐Inversion‐Recovery(FLAIR) images were rated and assigned a Fazekas‐score by neuroradiologist to quantify WMH. Vascular Risk Score(VRS), a composite of dichotomous(yes/no) 5‐clinical history‐items: hypertension, hypercholesterolemia, diabetes, smoking, and body‐mass‐index(≥ 30), was used. Result: Higher gray‐matter tissue‐magnetic‐susceptibilities (indicating iron‐concentrations ) in12‐ROIs were associated with higher GDS(Fig1). These patterns of associations remained after adjusting age, sex, diagnosis, and structural‐volume in regression analysis(Table‐2). Next, total‐iron‐content (susceptibility x regional‐volume) was estimated for ROIs. Principal Component analysis removed multicollinearity among 12‐ROIs, and only 1of the 3‐components obtained(Fig‐3a), was associated with GDS(Table‐3b). Regression using these independent component residuals showed the same ROIs remained associated with GDS(Table‐3c). Finally, Partial Least Squares Regression was done to determine the GDS‐items contributing to the associations, after adjusting age, sex, structural‐volume, Fazekas‐score and VRS(Fig‐4). Mostly the same ROIs were associated with apathy‐related symptoms(3 GDS‐items), but not depression symptoms(12‐items)(Table‐4). Conclusion: Iron‐deposits(QSM) in several brain‐regions were associated with apathy‐symptoms, after adjusting WMH, VRS and structural‐volume in 73 normal and impaired older‐individuals. Findings indicate possible mechanistic associations between brain iron‐deposition and apathy, distinct from depression.